Governing structural change and externalities in agriculture: toward a normative institutional economics of rural development - Martin Petrick (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2004)
The paper aims at a conceptual contribution to the normative economic analysis of rural de-velopment (RD) policies. RD is regarded as a problem of interaction between individuals; (lacking) structural change or the (missing) integration of externalities are therefore recon-structed as coordination rather than allocation problems. A social dilemma is taken as the paradigmatic core of normative institutional economics: how can potential gains from coop-eration be realised by way of institutional policy? Starting from a critique of the hitherto dominating welfare economics conception, three principles for institutional policy are de-rived: (1) the realisation of gains from cooperation as the normative, regulative idea, (2) in-centive-compatible self-regulation as the principle of individual action, and (3) institutional-ised competition as the institution-related principle. An application to rural credit markets demonstrates how these principles can be used to structure institutional policy of RD. – – Dieser Aufsatz versteht sich als konzeptioneller Beitrag zur normativen ökonomischen Ana-lyse ländlicher Entwicklungspolitik. Ländliche Entwicklung wird als ein Interaktionsproblem von Individuen angesehen; (fehlender) Strukturwandel oder die (Nicht-)Integration von Ex-ternalitäten werden daher als Koordinations- und nicht als Allokationsprobleme rekonstruiert. Ein soziales Dilemma wird als paradigmatischer Kern der normativen Institutionenökonomik eingeführt: wie können durch ordnungspolitische Maßnahmen mögliche Kooperationsgewin-ne realisiert werden? Ausgehend von einer Kritik der bisher dominierenden wohlfahrtsöko-nomischen Konzeption werden drei institutionenökonomische Politikprinzipien abgeleitet: (1) die Realisierung von Kooperationsgewinnen als normative, regulative Idee, (2) anreiz-kompatible Selbststeuerung als handlungsbezogenes Prinzip und (3) institutionalisierter Wett-bewerb als institutionenbezogenes Prinzip. Eine Anwendung auf ländliche Kreditmärkte zeigt, wie diese Prinzipien zur Strukturierung von ländlicher Entwicklungspolitik eingesetzt werden können.
urn:nbn:de:gbv:3:2-22552
Keywords: D63; D74; Q18; Q58; 330; rural development; institutional economics; welfare economics; social dilemma; ländliche Entwicklung; Institutionenökonomik; Wohlfahrtsökonomik; soziales Dilemma.